Determinants of occupational pension provision in Germany - Kathrin Dummann (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
Demographic change causes an undersupply of financial old age benefits within the statutory pay-as-you-go pension system in Germany. Therefore, the provision of occupational as well as private pensions has to be enhanced. However, there seems to be an undersupply of occupational pension provision particularly in small and medium sized enterprises (SMEs). Using survey data of the German Socio-Economic Panel (GSOEP) and the German SAVE survey, the present paper studies econometrically the determinants of occupational pension provision in Germany. It shows that occupational pensions depend not only on supply-side factors such as firm size and industry, but also on demand-side factors such as individual socio- demographic attributes and people's savings motives.
Keywords: C25; G23; J14; 330; Occupational Pensions; Retirement Provision; Demographic Change; SMEs; Betriebliche Altersversorgung; Alterssicherung; Klein- und Mittelunternehmen; Alternde Bevölkerung; Sparen